The princess of Albemarle : Amélie Rives, author and celebrity at the fin de siècle - Censer, Jane Turner, 1951- (Charlottesville : University of Virginia Press, 2022)
"Tells the life of Amelie Rives, a talented, privileged young woman who was one of the most famous women in the United States at the turn of the twentieth century. This account of Rives's substantial literary career and her personal saga provides insights into the limits imposed on and actions taken by ambitious, elite young women in the late nineteenth-century South. Censer contextualizes Rives's writings and actions within an American society and culture that were rapidly changing between 1880 and the 1920s and explores the ways in which she challenged and followed the gender conventions of her day"--
Notes -- Novels, Essays, and Stories by Amélie Rives -- Selected Bibliography -- Index
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on May 17, 2022).
JSTOR
Keywords: Rives, Amélie, -- 1863-1945.; Rives, Amélie, -- 1863-1945; Novelists, American -- 19th century -- Biography; Women and literature -- United States -- History -- 20th century; Women, White -- Southern States -- History -- 20th century; Upper class women -- Southern States -- History -- 20th century; Romanciers américains -- 19e siècle -- Biographies; Femmes et littérature -- États-Unis -- Histoire -- 20e siècle.; Blanches -- États-Unis (Sud) -- Histoire -- 20e siècle.; Femmes de la classe supérieure -- États-Unis (Sud) -- Histoire -- 20e siècle.; South (AL.; State & Local; United States; HISTORY; BIOGRAPHY & AUTOBIOGRAPHY; Novelists, American; Upper class women; Women and literature; Women, White; Southern States; United States; BIOGRAPHY & AUTOBIOGRAPHY / Historical; 1800-1999; Biographies; History